2022
DOI: 10.23887/jstundiksha.v11i2.45291
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant-Like Activity and Physicochemical Analysis of Essential Oils from Michelia alba and Plumeria alba Flowers

Abstract: Depression is a mental disorder with an increased prevalence. Other than conventional antidepressants, essential oils have been used in aromatherapy as a complementary and alternative medicine to reduce depression. In the current study, the antidepressant-like activity of the inhalation of essential oils from Michelia alba (MAEO) and Plumeria alba (PAEO) flowers was analyzed using the forced swim test. The immobility time of mice from tested groups was evaluated statistically by the non-parametric Kruskal Wall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Further preclinical studies have demonstrated anti-inflammatory 49 , antioxidant 51 , and anticancer 115 effects of flower essential oils in vitro , as well as sedative 71 , anti-anxiety 186 , anti-stress 226 , antidepressant 255 , analgesic, and antispasmodic 193 effects in animal models. Clinical studies confirm the effectiveness of essential flower oils for specific issues.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Further preclinical studies have demonstrated anti-inflammatory 49 , antioxidant 51 , and anticancer 115 effects of flower essential oils in vitro , as well as sedative 71 , anti-anxiety 186 , anti-stress 226 , antidepressant 255 , analgesic, and antispasmodic 193 effects in animal models. Clinical studies confirm the effectiveness of essential flower oils for specific issues.…”
Section: Discussionmentioning
confidence: 99%
“…The essential oil of the flowers of M. alba showed an antidepressant effect in animal experiments on mice, which, however, was weaker than that of L. angustifolia. The antidepressant effect was believed to be due to the presence of linalool and phenylethyl alcohol [255]. Many studies have already investigated the antidepressant-like effects of linalool.…”
Section: Other Activitymentioning
confidence: 99%
See 2 more Smart Citations